PENERAPAN CRASH DURATION PADA PELAKSANAAN PROJECT PANTRY - ANJASMARA, DEVANA; Sutowijoyo, Hendro (Program Studi Teknik Sipil Universitas Narotama, 2023)
The execution of a construction project will be said to be successful if the desired targets and goals are achieved and meet the cost, time and quality standards of construction. One of the important factors in working on a project is good time management. A project will be said to be efficient if the project implementation time is in accordance with the project planning schedule. The delay in the project itself means that the construction work does not go according to the predetermined plan, or takes longer than previously estimated. The occurrence of delays in workmanship also occurred in one of the pantry projects in the interior contractor. Given this incident, this study will focus on the object of analysis of the application of crash duration in the implementation of interior pantry projects. Keywords: Construction, Project Management, Project Planning Schedule, Crash Duration